A study on the collaborative governance constructs towards sustainable farming in Kelantan, Malaysia (Journal of Tropical Resources and Sustainable Science (JTRSS), 2025)
Sustainable farming has become imperative to harmonize economic growth, environmental conservation, and social equity. Kelantan farming sector faces critical challenges, including land degradation, water scarcity, climate vulnerabilities, and technological gaps. While collaborative governance (CG) is touted as a transformative approach to multi-stakeholder alignment, empirical evidence on its drivers and operational constructs in developing agrarian economies remains limited. This study bridges this gap by identifying the critical CG constructs and their drivers for sustainable farming in Kelantan. Through stratified sampling of 117 farmers across ten districts, the results show joint action (3.65) as the most vital CG component, followed by shared motivation (3.55) and principled engagement (3.53). Consequential incentives (3.73) and leadership (3.69) emerged as primary drivers, outperforming interdependence (3.46) and uncertainty (3.37). These findings demonstrate how incentives participation and strong leadership can enhance agricultural resilience against climate threats and provide a governance framework to improve stakeholder engagement in sustainable practices. The study offers policy-relevant insights for strengthening Kelantan's agricultural productivity and its contribution to Malaysia's food security.
Keywords: sustainable farming; collaborative governance; stakeholder; Kelantan